Treatment of cellulite with a bipolar radiofrequency, infrared heat, and pulsatile suction device: A pilot study - Rungsima Wanitphakdeedecha (2018)
Background: Very few therapeutic options have proven effective in the treatment of cellulite. Aims: To evaluate the effectiveness and adverse effects of a bipolar radiofrequency (RF), infrared (IR) heat and pulsatile suction device for the treatment of cellulite. Methods: Twelve subjects were treated with the RF-light-based device. All subjects were treated twice weekly for a total number of eight to nine treatments. Subjects were evaluated using standardized photographs, and measurements of body weight and circumference of treatment sites at baseline, immediately after the last treatment, and four weeks and one year after the last treatment. Clinical improvement scores of comparable photographs using a quartile grading scale (0 = <255%, 1 = 25-50%, 2 = 51-75%, 3 = >75% improvement) were judged independently by two non-treating dermatologists after the series of treatment. Results: The average body weights at baseline, immediately after the last treatment, and four weeks and one year after the complete treatment were 56.30, 56.05, 56.23, and 56.53 kg, respectively. The average circumferential reductions of the abdomen and thigh at the last treatment visit were 5.17 ± 1.04 cm (6.32% ± 1.82%) and 3.50 ± 2.16 cm (6.23 ± 3.58%), respectively. At four weeks after the last treatment, the average circumferential reductions of the abdomen and thigh were sustained at 3.17 ± 2.75 cm (4.04% ± 3.69%) and 3.50 ± 2.04 cm (6.26% ± 3.52%), respectively. At one year follow-up visit, the average circumferential reductions of the abdomen and thigh were maintained at 3.83±0.76 cm (4.64% ± 1.15%) and 3.13 ± 3.54 (5.50% ± 6.12%), respectively. Average clinical improvement scores of the abdomen and thigh after the series of treatments were 0.75 (corresponding to ∼25% improvement), and 1.75 (corresponding to ∼50% improvement), respectively. Conclusions: A bipolar RF, IR heat and pulsatile suction device provides a beneficial effect on reduction of abdomen and thigh circumference, and smoothening of the cellulite. © 2006 Blackwell Publishing.